2013
DOI: 10.1097/dcr.0b013e318298e36b
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Partial Tumor Regression After Preoperative Chemoradiotherapy for Rectal Cancer

Abstract: Partial tumor response is associated with a 50% improvement in disease-free survival and should be considered as a favorable prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 45 publications
6
64
1
3
Order By: Relevance
“…For example, none of the patients in our study showed a complete TRG response; 82.4% showed a poor response and 17.6% showed a minimal to moderate response. However, a meta-analysis performed by Lee et al indicated that even partial tumor regression after preoperative chemoradiotherapy improves DFS, and should be considered as a favorable prognostic factor [21]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, none of the patients in our study showed a complete TRG response; 82.4% showed a poor response and 17.6% showed a minimal to moderate response. However, a meta-analysis performed by Lee et al indicated that even partial tumor regression after preoperative chemoradiotherapy improves DFS, and should be considered as a favorable prognostic factor [21]. …”
Section: Discussionmentioning
confidence: 99%
“…A number of recent trials of long-course chemoradiotherapy optimization (including this one) have had tumor regression at the time of surgery as the primary endpoint (7, 9, 31, 32). However, while tumor regression is a prognostic marker (2628) this does not imply that it is a valid surrogate of a relevant clinical endpoint in rectal cancer (28, 30, 33). Although there was no difference between the treatment arms for the primary trial endpoint (pCR), we found a significant increase in the rate of major response in the brachytherapy boost arm (41% vs 28%).…”
Section: Discussionmentioning
confidence: 99%
“…Rectal cancers account for 30% -35% of patients with colorectal cancers (2). Various tumor markers and clinical risk factors were reported to be associated with the overall prognosis of rectal cancers, including pre-treatment levels of carcinoembryonic antigen (CEA), pathological T and N stage, tumor differentiation grade, and presence of lymphovascular invasion (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%